A new insight into the effect of starch nanocrystals in the retrogradation properties of starch - Johnsy George; Sruthy G. Nair; R. Kumar; A.D. Semwal; Cherakkathodi Sudheesh; Aaliya Basheer; Kappat Valiyapeediyekkal Sunooj (Food Hydrocolloids for Health, 2021)
Starch nanocrystals (SNC) are having the potential to control the retrogradation of starch; however, their efficacy to control retrogradation in starch was not fully understood. In this investigation, starch nanocrystals (SNC) were synthesized from rice (RS) and wheat (WS) starches, and their influence on short and long-term retrogradation properties of the starch-SNC mixture was extensively studied. Starch-SNC mixture was prepared by mixing SNC of rice and wheat with their respective starches in different proportions (5%, 10%, and 15%). The addition of SNC to the respective starch samples significantly (p ≤ 0.05) reduced the short-term retrogradation properties of starch-nanocrystal mixtures. The non-nucleated amylopectin units present in the starch-nanocrystal mixture inhibited the reassociation of amylose chains resulted in lower short-term retrogradation of the starch-nanocrystal mixtures. The setback and final viscosity of the starch-nanocrystal mixture decreased with an increase in the SNC concentration. Increased values of ΔHR (enthalpy of retrogradation), hardness, syneresis, and lower freeze-thaw stability of starch–SNC mixtures indicated that long-term retrogradation was not reduced due to the addition of SNC. Hence, the present study confirms the role of SNC as a promising additive for retarding short-term retrogradation properties of various starchy products.